Toy story = Oyuncak hikayesi - Lasseter, John (Disney : Pixar Animation Studios, 2015)
A cowboy doll is profoundly threatened and jealous when a new spaceman figure supplants him as top toy in a boy's room.
3-6.
K-3.
Language : Turkish, English, German.
Subtitle : Turkish, English, German.
Keywords: Movie -- animated films; Movie -- Kids/Family.; Toys -- Movie